Islam's Position on the Experimental Science ond Modern Technology | موقف الإسلام من العلم التجريبي والتكنولوجيا المعاصرة - Muhammad Ali Abdul Azhim (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2011)
The study is about attention of Islam for knowledge in general and especially inexperimental and modern technology. According to Islam, knowledge isfoundation for developing human being, spiritually, physically and rationally,and it is foundation of civilization and development in all its meaning.Changing human being from the less development to the development andfrom the darkness to the lightness. This study contains four main sub topics:Islam’s support and motivation for research, Muslim scholar’s effort in theirscientific achievement, scientific evident of the Muslim’s initiation in usingexperimental method, and using modern technology. The study refers to theQuranic and Hadis texts, opinions of classical and modern scholars, bothMuslims and non Muslims, and also both classical and modern books.